ALlY ANCED OXIDATION PROCESS OF WASTEWATER CONT i\INING OXYTETRACYCLINE ANTIBIOITIC CONTAMINANT USING UV/H20 2 SYSTEM - , ANISA UR RAHMAH (2015)
Oxytetracycline hydrochloride (OTC) is a widely used antibiotic for treating bacterial infection, especially in livestock production. Eventhough detected in concentration ranging from f.!g/L to mg/L, its continuous input to the environment have increased the awareness of oxytetracycline as the emerging persistent organic pollutant. Contaminations of antibiotics have caused the formation of resistances in pathogenic bacteria, damage the internal organ of aquatic animal, trigger the allergic reactions and contribute to the selection of antibiotic-resistant bacteria in the human body. The oxytetracycline antibiotic is biologically active. Therefore, complete removal by using conventional wastewater treatment, such as biodegradation, could not be achieved. Advanced Oxidation Processes (AOP's), as the chemical degradation, utilize highly reactive species for attacking the recalcitrant organics and further mineralizes the contaminant into inorganic molecule that benign to our environment.